2017
DOI: 10.1111/dome.12109
|View full text |Cite
|
Sign up to set email alerts
|

Passive Conformism in Academia: Saudi Organization, Education, and Technology

Abstract: Academia is expected to act as a cognitive arena in which members intellectually challenge one another, problematize social structures, and destabilize dominant ideologies. It is, supposedly, a cognitively unstable environment wherein intellectualism pushes social boundaries and acts as an agent for social change. It is a training camp wherein people come to be trained in the practice of critical thinking. Hence, one would imagine that academia would be the last place to find passive conformism. However, does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This is the main reason for our participants agreeing with most items. Interestingly, this is possibly another example of high conformism that characterizes Saudi Arabia (Gahwaji, 2008;Al-Rasheed, 2013;Al Lily and Alhazmi, 2017). For instance, scholars found that Saudi students have high conformity with the Communicative Language Teaching approach (Wajid and Saleem, 2017) despite having continually low English proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This is the main reason for our participants agreeing with most items. Interestingly, this is possibly another example of high conformism that characterizes Saudi Arabia (Gahwaji, 2008;Al-Rasheed, 2013;Al Lily and Alhazmi, 2017). For instance, scholars found that Saudi students have high conformity with the Communicative Language Teaching approach (Wajid and Saleem, 2017) despite having continually low English proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitous nature of social media sites affords users extraordinary opportunities for participation, collaboration, and access to information. According to studies by Al Lily & Alhazmi (2017), a sizable percentage of Jordanians use Twitter, Instagram, Snapchat, and WhatsApp regularly.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 99%